2020
DOI: 10.3390/ijms21186642
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma GRA16 Inhibits NF-κB Activation through PP2A-B55 Upregulation in Non-Small-Cell Lung Carcinoma Cells

Abstract: Nuclear factor kappa B (NF-κB) activation is a well-known mechanism by which chemoresistance to anticancer agents is reported. It is well-known that irinotecan as a chemotherapeutic drug against non-small-cell lung carcinoma (NSCLC) has limited anticancer effect due to NF-κB activation. In this study, we propose the novel role of GRA16, a dense granule protein of Toxoplasma gondii, as an anticancer agent to increase the effectiveness of chemotherapy via the inhibition of NF-κB activation. To demonstrate this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…GRA16 interacts with host ubiquitin-specific protease 7 and protein phosphatase 2A to manipulate cell-cycle progression and restore p53 pathway through five putative nuclear sequences ( Bougdour et al., 2013 ). GRA16 also improves the treatment efficacy of irinotecan, a chemotherapeutic drug, by inhibiting the activation of nuclear factor kappa B (NF-κB) in non-small-cell lung carcinoma H1299 cells ( Seo et al., 2020 ). Furthermore, as the main regulator of immune and inflammatory processes, NF-κB is also regarded as a tumor-immunosurveillance factor that mediates the crosstalk of many transcription factors [such as the tumor necrosis factor receptor-associated factors (TRAFs)] and regulates the secretion of cytokines (such as TNFα, IL-1, and IL-6), cell proliferation, and apoptosis ( Hoesel and Schmid, 2013 ).…”
Section: T Gondii Molecules Participate In Anti-tumor Immuni...mentioning
confidence: 99%
“…GRA16 interacts with host ubiquitin-specific protease 7 and protein phosphatase 2A to manipulate cell-cycle progression and restore p53 pathway through five putative nuclear sequences ( Bougdour et al., 2013 ). GRA16 also improves the treatment efficacy of irinotecan, a chemotherapeutic drug, by inhibiting the activation of nuclear factor kappa B (NF-κB) in non-small-cell lung carcinoma H1299 cells ( Seo et al., 2020 ). Furthermore, as the main regulator of immune and inflammatory processes, NF-κB is also regarded as a tumor-immunosurveillance factor that mediates the crosstalk of many transcription factors [such as the tumor necrosis factor receptor-associated factors (TRAFs)] and regulates the secretion of cytokines (such as TNFα, IL-1, and IL-6), cell proliferation, and apoptosis ( Hoesel and Schmid, 2013 ).…”
Section: T Gondii Molecules Participate In Anti-tumor Immuni...mentioning
confidence: 99%
“…Regarding inflammation, data about CPT and its derivatives are still unclear. Indeed, it has been demonstrated that CPT and CPT-11 induce activation of the NF-κB pathway in a variety of human carcinoma cell lines, a mechanism thought to contribute to resistance to chemotherapy [41][42][43]. In addition, SN38, the active metabolite of CPT-11, has been shown to increase CXCL8 secretion by enhancing the phosphorylation of MAP kinases in HCT8 cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Coincidentally, the secreted GRA15 was confirmed to localize to the endoplasmic reticulum and to activate innate immune and stimulator of interferon genes (STING) responses by promoting polyubiquitination at Lys-337 and oligomerization in a tumor necrosis factor (TNF) receptor-associated factor (TRAF) protein-dependent manner [ 24 ]. In addition, the GRA16 displayed the ability to break the chemoresistance of irinotecan by inhibiting nuclear factor kappa B (NF-κB) via a PP2A-B55/AKT/NF-κB p65 pathway against non-small-cell lung carcinoma (NSCLC) [ 25 ]. Recently, the fact that the small intestine (SI) exhibited low tumorigenesis or metastatic growth from distant tumors attracted attention.…”
Section: Antitumor Effect Of Parasitic Productsmentioning
confidence: 99%